2015
DOI: 10.3892/or.2015.4291
|View full text |Cite
|
Sign up to set email alerts
|

RSK4 knockdown promotes proliferation, migration and metastasis of human breast adenocarcinoma cells

Abstract: Abstract. RSK4 has been shown to inhibit the growth of certain cancer cells. The aim of this study was to construct a lentiviral vector of RSK4-shRNA (Lenti-RSK4-shRNA) to specifically block the expression of RSK4 in the human breast adenocarcinoma cell line MCF-7, and investigate the effect of the RSK4 gene on cell proliferation and invasion in vitro and in vivo. Lenti-RSK4-shRNA was stably transfected into MCF-7 cells. RSK4 mRNA and protein expression were measured by fluorescence quantitative RT-PCR and wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
4
13
1
Order By: Relevance
“…Further investigation also showed that the downregulation of RSK4 expression in breast cancer cells is mediated by gene expression inhibition through promoter hypermethylation, which frequently occurs in breast cancer cells (13). Consistently, RSK4 knockdown in human breast adenocarcinoma cells significantly promoted proliferation and migration, which further confirms the role of RSK4 in the development and progression of breast cancer (14).…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…Further investigation also showed that the downregulation of RSK4 expression in breast cancer cells is mediated by gene expression inhibition through promoter hypermethylation, which frequently occurs in breast cancer cells (13). Consistently, RSK4 knockdown in human breast adenocarcinoma cells significantly promoted proliferation and migration, which further confirms the role of RSK4 in the development and progression of breast cancer (14).…”
Section: Introductionsupporting
confidence: 53%
“…cells further confirmed its critical role in regulating breast cancer progression. Combined with other publications about RSK4 and breast cancer (3,13,14), recent evidence provides an important research basis for the future application of RSK4 in breast cancer screening, diagnosis and therapy, although large prospective clinical studies should be performed to establish its predictive value in patients with breast cancer.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It can regulate cell survival, angiogenesis, tissue invasion, DNA damage resistance, and EMT . Of the six mRNAS identified in the neurotrophin signaling pathway targeted by the miRNAs (Table ) that showed at least 2× fold change in level, RPS6KA6 and PIK3R1 tumor suppressors that work to inhibit the oncogene PIK3CA were both decreased . SORT1 mRNA was also decreased.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] Several reports have identified RSK4 as a tumor suppressor in the colon, breast, and renal carcinomas. [10][11][12][13] The over-expression of RSK4 could restrict cell growth, demonstrating anti-invasive and anti-metastatic effects. 14,15 In addition, RSK4 is recommended as a useful prognostic marker in patient evaluation.…”
Section: Introductionmentioning
confidence: 99%